Willingness to Donate Organs Among People Living With HIV. (1st September 2018) - Nguyen, Anh Q.; Anjum, Saad K.; Halpern, Samantha E.; Kumar, Komal; Van Pilsum Rasmussen, Sarah E.; Doby, Brianna; Shaffer, Ashton A.; Massie, Allan B.; Tobian, Aaron A.R.; Segev, Dorry L.; Sugarman, Jeremy; Durand, Christine M.
Abstract : Background: With passage of the HIV Organ Policy Equity (HOPE) Act, people living with HIV (PLWH) can donate organs to PLWH awaiting transplant. Understanding knowledge and attitudes regarding organ donation among PLWH in the United States is critical to implementing the HOPE Act. Methods: PLWH were surveyed regarding their knowledge, attitudes, and beliefs about organ donation and transplantation at an urban academic HIV clinic in Baltimore, MD, between August 2016 and October 2016. Responses were compared using Fisher exact and χ 2 tests. Results: Among 114 survey respondents, median age was 55 years, 47.8% were female, and 91.2% were African American. Most were willing to be deceased donors (79.8%) or living donors (62.3%). Most (80.7%) were aware of the US organ shortage; however, only 24.6% knew about the HOPE Act, and only 21.1% were registered donors. Respondents who trusted the medical system or thought their organs would function adequately in recipients were more likely to be willing to be deceased donors ( P < 0.001). Respondents who were concerned about surgery, worse health postdonation, or need for changes in HIV treatment because of donation were less likely to be willing to be living donors ( P < 0.05 for all). Most believed that PLWH should be permitted to donate (90.4%) and that using HIV+ donor organs for transplant would reduce discrimination against PLWH (72.8%). Conclusions: Many of the PLWH surveyed expressed willingness to be organ donors. However, knowledge about the HOPE Act and donor registration was low, highlighting a need to increase outreach. Abstract : Supplemental Digital Content is Available in the Text.